PSMA as a Target for Advanced Prostate Cancer: A Systematic Review - Belbina, Safiya-Hana; Schmolze, Mia Rose; Gereta, Sofia; Laviana, Aaron A. (Frontiers in Urology, 2022)
Objective Prostate-specific membrane antigen (PSMA) is a cell-surface protein widely expressed on most prostate cancer cells that has rapidly emerging clinical utility in the realm of prostate cancer. This systematic review aims to evaluate the efficacy as well as cost-effectiveness of PSMA in the roles of diagnosis and treatment in prostate cancer management. Background The use of PSMA in the initial staging of patients, early detection of recurrence, and response monitoring are critical to improving prostate cancer treatment. We performed a systematic review of the role of Gallium-68 (68Ga)-PSMA in the initial detection of prostate cancer and detection of biochemical recurrence (BCR) as well as the role of Lutium-177 (177Lu)-PSMA in theranostics. We also investigated the cost-effectiveness of both ligands in comparison to the current standard of care. Methods In February 2022 we performed a systematic and comprehensive review of the existing literature. We identified and screened articles published from 1983 up to January 2022 through PubMed. Only 1 study was included prior to 2011. We included articles that investigated the efficacy or cost-effectiveness of PSMA in prostate cancer detection and therapy. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRSIMA) guidelines eligible articles were selected, and relevant information was extracted from the original articles. Results A total of 26 articles were included in the analysis of this systematic review. These studies were heterogeneous and were comprised of five prospective studies including 336 patients, three retrospective analyses including 540 patients, one phase III trial, one survival analysis, one randomized control trial, three systematic reviews, three meta-analyses, two in-vivo studies, three reviews, and four cost analyses. Conclusion The diagnostic and therapeutic role of PSMA appears more efficacious and potentially less expensive than the standard treatment for patients with BCR of prostate cancer. Current evidence suggests PSMA will also fill an unmet need in initial diagnostics of prostate cancer and ligand therapy. However, a consensus has not yet been reached on cost-effectiveness of PSMA and further prospective studies are needed.